The management of heart failure in Sweden—the physician’s perspective: a survey - Ferrannini, Giulia; Biber, Mattia Emanuele; Abdi, Sam; Ståhlberg, Marcus; Lund, Lars H.; Savarese, Gianluigi (Frontiers in Cardiovascular Medicine, 2024)
Aims To assess the barriers to guideline-directed medical therapy (GDMT) use in heart failure (HF), diagnostic workup and general knowledge about HF among physicians in Sweden. Methods A survey about the management of HF was sent to 828 Swedish physicians including general practitioners (GPs) and specialists during 2021–2022. Answers were reported as percentages and comparisons were made by specialty (GPs vs. specialists). Results One hundred sixty-eight physicians participated in the survey (40% females, median age 43 years; 41% GPs and 59% specialists). Electrocardiography and New York Heart Association class evaluations are mostly performed once a year by GPs (46%) and at every outpatient visit by specialists (40%). Echocardiography is mostly requested if there is clinical deterioration (60%). One-third of participants screen for iron deficiency only if there is anemia. Major obstacles to implementation of different drug classes in HF with reduced ejection fraction are related to side effects, with no significant differences between specialties. Device implantation is deemed appropriate regardless of aetiology (69%) and patient age (86%). Specialists answered correctly to knowledge questions more often than GPs. Eighty-six percent of participants think that GDMT should be implemented as much as possible. Most participants (57%) believe that regular patient assessment in nurse-led HF clinics improve adherence to GDMT. Conclusion Obstacles to GDMT implementation according to physicians in Sweden mainly relate to potential side effects, lack of specialist knowledge and organizational aspects. Further efforts should be placed in educational activities and structuring of nurse-led clinics.